ON THE DATA-SET STRUCTURE FOR TRAINING GENERATIVE NEURAL NETWORKS IN PROTEIN DESIGN - Гайша, Олександр; Гайша, Олена (SWorldJournal, 2024)
The paper considers the ways of normalizing a data set that can be used to train neural networks used for designing proteins or other large organic molecules with a complex structure. The paper considers the ways of translational transformation of coordi